DETERMINANT FACTORS INFLUENCING CREDIT DISTRIBUTION IN THE INDONESIAN BANKING INDUSTRY - Odilia, Diva Nadya; Ma’ruf, Aminudin (JOURNAL of APPLIED BUSINESS and BANKING (JABB), 2026)
The banking sector plays a crucial role in supporting economic growth through credit intermediation, particularly in developing countries such as Indonesia where the financial system is highly concentrated. This study aims to examine the factors influencing credit distribution among systemically important banks in Indonesia during the period 2015–2024. The research applies a quantitative approach using monthly panel data from four major banks in Indonesia and employs a fixed effects regression model. The findings indicate that bank size and liquidity significantly encourage credit distribution, while credit risk acts as a major constraint on lending activities. Meanwhile, profitability indicators and inflation show no significant influence, and the policy interest rate has a slight negative effect on credit growth. These results suggest that internal bank characteristics play a more dominant role than external macroeconomic conditions in determining lending behavior. Therefore, strengthening prudential regulation and implementing appropriate macroprudential policies are important to support sustainable credit growth and maintain financial stability in Indonesia.